Representing French and Francophone Studies with Michel Serres. Issue 2 (July 2019) - WATKIN, Christopher
Abstract : What do we talk about when we talk about French and Francophone Studies? If we could approach French Studies as a Martian anthropologist seeking to understand its rationale but ignorant of its history, what might we conclude? As it happens, such disciplinary questions engage one of the major concerns at the heart of French philosophy over recent decades: the problem of the same and the other. Departing from the orthodox accounts of sameness and otherness, the work of polymath and académicien Michel Serres offers us a new approach to understanding the relation between identity and alterity, an approach he explores in terms of the motif of chirality. Serres not only delivers a radical challenge to one of the most fundamental commonplaces of recent French thought, namely the opposition between sameness and alterity, but in so doing he also helps us to find new ways of understanding and articulating the nature and specificity of French and Francophone Studies today.